Impact of sexual maturation on upper and lower limb strength on adolescents - Diego Augusto Santos Silva; Antonio Cesar Cabral de Oliveira (Universidade Federal de Santa Catarina, 2010)
Biological and sexual maturation is one of the most important variables for the interpretation of the results of performance and health studies analyzing upper (ULS) and lower limb strength (LLS), with performance varying according to maturation stage. Since menarche is a marker of maturation, the aim of this study was to compare ULS and LLS between adoles-cents who already had their first menarche and those who did not. A cross-sectional study was conducted on 128 adolescents aged 11 to 14 years and divided into two groups: adolescents who did not report the presence of menarche (n=72), adolescents who reported menarche (n=56). ULS was evaluated by the hand grip test using a manual dynamometer. The vertical jump test was used for the evaluation of LLS. Descriptive statistics and covariance analysis (ANCOVA) were used for data analysis, with age, body weight, height and BMI as covariables. The level of significance was set at 5% (p<0.05). ULS differed between G1 (17.8±4.4 kg/f) and G2 (21.5±3.9 kg/f) (p<0.05). However, no difference in LLS was observed between groups (G1 = 23.7±6.7 cm; G2 = 24.1±6.7 cm). The presence of menarche might be one of the events improving the performance in the ULS test, but the same cannot be inferred when analyzing LLS.